A FRET Probe for Cell‐Based Imaging of Ganglioside‐Processing Enzyme Activity and High‐Throughput Screening1. Issue 18 (10th March 2015) - Yang, Guang‐Yu; Li, Caishun; Fischer, Michael; Cairo, Christopher W.; Feng, Yan; Withers, Stephen G.
Abstract Gangliosides are important signaling molecules in the cell membrane and are processed by several enzymes. Deficiencies in these enzymes can cause human lysosomal storage diseases. Building an understanding of the pathways of glycosphingolipid catabolism requires methods for the analysis of these enzymatic activities A GM3‐derived FRET probe was synthesized chemoenzymatically for the detection and quantitation of a range of ganglioside‐degrading enzymes, both in cell lysates and in living cells. This is the first substrate that enables the ratiometric fluorogenic assay of sphingolipid ceramide N‐deacylase and endoglycoceramidase and can detect and localize neuraminidase activity in living cells. It is therefore a valuable tool for building a better understanding of membrane‐confined enzymology. It also enables the robust and reliable assay of ganglioside‐degrading enzymes in a microtiter plate, thus opening the door to screening for novel or engineered biocatalysts or for new inhibitors.